2008
DOI: 10.1016/j.ijgo.2008.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of loop electrosurgical excision procedure in a low‐resource setting

Abstract: LEEP was associated with minimal complications and acceptable cure rates in a low-resource setting, although women with larger lesions had lower cure rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 18 publications
2
27
1
1
Order By: Relevance
“…LEEP has rapidly gained acceptance as a procedure providing specimens for pathological study; it can be performed in an outpatient setting and has an acceptable success rate and low rate of complications [2][3][4][5]. This low-cost procedure is also technically easy to teach and use.…”
Section: Introductionmentioning
confidence: 99%
“…LEEP has rapidly gained acceptance as a procedure providing specimens for pathological study; it can be performed in an outpatient setting and has an acceptable success rate and low rate of complications [2][3][4][5]. This low-cost procedure is also technically easy to teach and use.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods such as visual inspection after application of Lugol's iodine or with magnifying device (VIAM; ref. 45), as well as loop electrosurgical procedure (46), were likewise shown to be feasible and effective screening methods.…”
Section: Discussionmentioning
confidence: 98%
“…Wright et al has reported cure rate of LEEP to be 94% with large electrode and 80% with small electrode 9 while Rema et al stated the effectiveness of 93% in CIN 1, 85.5% in CIN 2 and 72% in CIN 3. 10 Margin status is used as a predictor for residual or recurrent disease, although several studies have reported that margin status does not adequately predict probability of residual disease. 12 In our study 22 (78.5%) had margin negative; six cases (21.5%) had focal peripheral margin positive which contradicts the study by Kim et al where resected margins were positive in 81.39%.…”
Section: Discussionmentioning
confidence: 99%